Vitamin D binding protein polymorphisms significantly impact vitamin D status in children - Danforth A. Newton; John E. Baatz; Mark S. Kindy; Sebastiano Gattoni‐Celli; Judy R. Shary; Bruce W. Hollis; Carol L. Wagner (2019)
Polymorphic alleles of the vitamin D (vitD)-binding protein (VDBP) gene are associated with discriminatory differences in circulating concentrations of 25-hydroxyvitamin D (25-D), the indicator of vitD status (sufficiency defined by the Endocrine Society as ≥75 nmol/L). Within a diverse group of children, we hypothesized that reaching recommended daily allowance (RDA) of vitD intake would have differential impact on vitD status depending on VDBP variability. VDBP alleles (Gc1S, Gc1F, Gc2) in 123 children (1–4 annual visits/child; ages 1–8 years) were compared for relationships with serum 25-D concentrations and daily vitD intake. In African-American children, reaching the vitD RDA was associated with significantly higher mean serum 25-D concentrations for the 20% carrying the VDBP 1S allele than for the large majority without this allele (77 vs. 61 nmol/L 25-D; p = 0.038). Children with the Gc1S/1S homozygous genotype (30% Caucasians, 24% Hispanics, 2% African-Americans) who met RDA had 51% (39 nmol/L) greater mean serum 25-D than those below RDA (p < 0.0001). VDBP genetic variability was a significant factor affecting childhood vitD status when following RDA guidelines. This study may inform public health policy of uniformity in recommended childhood vitD dosage, especially regarding racially/ethnically associated disparities.